The Ethics of Parent-Child Communication in Islam: Insights Derived from the Qur'an and Sunnah - Puji Asriani; Wahyudi Wahyudi (Bulletin of Indonesian Islamic Studies, 2025)
Communication between parents and children is vital in shaping character, attitudes, and the overall quality of family relationships. In Islam, this communication is regarded as an essential aspect of education and moral guidance. This study seeks to delve into the ethics of communication between parents and children as grounded in Islamic teachings by examining the normative values present in the Qur'an and Hadith, as well as their relevance in contemporary Muslim family life. The research employs a qualitative approach, conducting a literature review that analyzes primary sources, including verses from the Qur'an and Hadith, along with secondary sources such as books, scholarly articles, and academic studies addressing family communication and Islamic education. The findings reveal that Islamic communication ethics emphasize principles such as gentleness (qaulan layyinan), honesty, patience, wisdom, exemplary behavior, and mutual respect between parents and children, all of which are foundational for fostering harmonious family relationships rooted in spiritual values. Additionally, ethical communication has been found to significantly contribute to instilling moral values, enhancing emotional closeness, and preventing conflicts within families. This study offers both theoretical insights into the development of family communication studies based on Islamic values and practical guidance for parents and educators in implementing ethical communication practices to cultivate families that are socially, emotionally, and spiritually fulfilled.